Analisis Efisiensi Water Tube Boiler Berbahan Bakar Fiber dan Cangkang Sawit di PT Dhamasraya Palma Sejahtera - Jatmiko Edi Siswanto; Generousdi Generousdi (Journal of Electrical Power Control and Automation (JEPCA), 2022)
Palm oil mill processing companies in their operations use Water Tube Boilers which are fueled by shells and fiber. Boiler or Steam Kettle is a container that contains water or other fluids to be heated. Boiler with a capacity of 30 tons. In general, every machine produced by the factory is always equipped with a handbook/instruction book on how to install, maintain and operate it. Likewise with the boilers in the Company there are manuals regarding specifications for operation, maintenance, installation, and others. of various kinds of boiler fuel mixtures for combustion can produce different thermic efficiencies depending on the percentage of the mixture, in this study the results of laboratory tests obtained the calorific value of the fuel mixture of 70% fiber and 30% shells had the highest calorific value, namely 4604.7 Cal /g. The highest boiler efficiency value produced was 53.9% using 100% shell fuel, the efficiency using 100% fiber fuel was 51% and the lowest boiler efficiency value produced was 49.5% using a mixed fuel of 70% fiber and 30 % shell.